Resilient Care of Community Spirituality. The Experience of the Muslim Young-BG Association - Raccagni, Dalila; Sarzilla, Elena (INSTED: Interdisciplinary Studies in Education & Society, 2025)
This paper presents an action-research study that investigates the spiritual experiences of young Muslims in Bergamo, Italy, particularly within the Islamic Cultural Center located beneath a busy overpass on Via Rosa. This center serves not only as a place of worship, but also as a vital site for community engagement and cultural identity formation amid the challenges posed by its unconventional location. The research explores how these young individuals navigate their spirituality and cultivate communal bonds despite the limitations of the physical space, which is often characterized as inadequate and disruptive. Through creative methodologies, including poetic expression, participants articulate their resilience and adaptability in confronting environmental adversity. The findings reveal a profound commitment to spirituality that transcends the constraints of their surroundings, highlighting the need for inclusive and supportive spaces that reflect the aesthetic and functional aspirations of the Muslim community in Italy.